Transformation Of Korbrimob Intelligence Functions In The Effort Of Polri Operational Reform In Handling The Papua Armed Criminal Group (Kkb) Conflict: A Study Of Local Papuan Community Perceptions Of Korbrimob Intelligence - Listra Kogoya; Novi Indah Earlyanti; Oscarius Yudhi Ari Wijaya; Elvianus Laoli (LP2M IAIN Palopo, 2026)
This study examines the transformation of the intelligence function of the Mobile Brigade Corps (Korps Brimob/Korbrimob) within the framework of the Indonesian National Police’s (Polri) Operational Reform in handling conflicts involving Armed Criminal Groups (Kelompok Kriminal Bersenjata/KKB) in Papua. The main focus of the research is the perception of local Papuan communities toward the performance of Korbrimob’s intelligence, particularly in the implementation of a humanistic and intelligence-based approach.. This research employs the theories of bureaucratic reform, intelligence theory, SWOT analysis, conflict theory, and the concept of trust as analytical frameworks. The method used is a case study method with a qualitative research approach. Primary data were obtained through interviews with key informants, while secondary data were collected from relevant supporting documents.. The findings indicate that the transformation of Korbrimob’s intelligence function has marked a paradigm shift from a repressive approach to a more predictive, preventive, and humanistic approach. Public perceptions of the intelligence function vary and are influenced by historical experiences of conflict, social trauma, and the implementation of approaches based on dialogue and respect for local values. The success of this transformation is strongly influenced by supporting factors such as the professionalism of personnel, accountability, and community involvement, while also being constrained by challenges including structural inequalities, policy inconsistencies, and limited resources. In conclusion, the transformation of Korbrimob’s intelligence function plays a strategic role in managing KKB conflicts in Papua and in increasing public trust. This transformation serves not only as a security instrument but also as a means of strengthening state legitimacy and social integration in conflict areas, through a professional, humanistic, and community-oriented approach.